2008
DOI: 10.1093/rheumatology/ken305
|View full text |Cite
|
Sign up to set email alerts
|

Gout and the risk of type 2 diabetes among men with a high cardiovascular risk profile

Abstract: These findings from men with a high cardiovascular risk profile suggest that men with gout are at a higher future risk of type 2 diabetes independent of other known risk factors. These data expand on well-established, cross-sectional associations between hyperuricaemia, gout and the metabolic syndrome, and extend the link to the future risk of type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
134
0
8

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(149 citation statements)
references
References 41 publications
7
134
0
8
Order By: Relevance
“…Previous studies as well as this study reported that serum uric acid is more closely associated with impaired fasting glucose [34]- [40].…”
Section: Discussionsupporting
confidence: 63%
“…Previous studies as well as this study reported that serum uric acid is more closely associated with impaired fasting glucose [34]- [40].…”
Section: Discussionsupporting
confidence: 63%
“…В послед-ние годы стали появляться работы, свидетель-ствующие, что она может быть фактором рис-ка (ФР) развития болезней, которые могут обусловливать сокращение продолжительно-сти жизни пациентов [4][5][6], однако данные исследования немногочисленны и этот воп-рос требует дополнительного изучения.…”
Section: коморбидные заболевания при подагреunclassified
“…A large epidemiological study [23] of Japanese adult men showed that an elevation of serum uric acid levels increased the risk of type 2 diabetes. Dehghan et al [24] demonstrated that serum uric acid is a strong and independent risk factor for diabetes in a 10-year follow-up study. Other studies [25] demonstrated a significant linear regression between serum uric acid levels and incident type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%